Disruption of remote education in the university program for adults in times of covid-19 - Romero Escalante, Victor Fabian (2020)
The objective of this research was to compare the perceptions that students of the adult training program of the Cesar Vallejo University School of Administration have on the disruption of remote modality in classroom education. The research focus was quantitative, with a quasi-experimental design and an ex-facto comparative-causal level. The sample was made up of 25 students to whom the Zoller (1992) perceptions questionnaire was applied, an instrument that demonstrated validity and reliability. The results indicate that there are significant differences between the groups (t = 4.67; sig. = 0.000 <0.05), the highest mean was the classroom education modality, concluding that the students of the adult training program have resistance to changing modality in education.